Adaptations to practice and resilience in a paediatric major trauma centre during a mass casualty incident. (February 2022) - MacKinnon, Ralph J.; Slater, David; Pukk-Härenstam, Karin; von Thiele Schwarz, Ulrica; Stenfors, Terese
Abstract: Background: Innovation and human adaptation in the face of unfolding catastrophe is the cornerstone of an effective systemwide response. Capturing, analysing, and disseminating this is fundamental in developing resilience for future events. The aim of this study was to understand the characteristics of adaptations to practice early in a paediatric major trauma centre during a mass casualty incident. Methods: A qualitative interview study of 40 healthcare staff at a paediatric major trauma centre in the immediate aftermath of a terrorist bombing was conducted. An inductive thematic analysis approach was used, followed by a deductive analysis of the identified adaptations informed by constructs of resilience engineering. Results: Five themes of adaptations to practice that enhanced the resilient performance of the hospital were identified: teamworking; psychologically supporting patients, families, and staff; reconfiguring infrastructure; working around the hospital electronic systems; and maintaining hospital safety. Examples of resilience potential in terms of respond, monitor, anticipate, and learn are presented. Conclusions: Our study shows how adaptations to practice sustained the resilient performance of a paediatric major trauma centre during a mass casualty incident. Rapid, early capture of these data during a mass casualty incident provides key insights into enhancing future emergency preparedness, response, and resilience planning.